Early Results of Total Coronary Revascularization via Left Anterior Thoracotomy - Sellin, Christian; Asch, Silke; Belmenai, Ahmed; Mourad, Fanar; Voss, Meinolf; Dörge, Hilmar (The Thoracic and Cardiovascular Surgeon, 2022)
Background Avoidance of sternotomy while preserving complete revascularization remains challenging in multivessel coronary disease. Technical issues and in-hospital outcomes of total coronary revascularization via a small left anterior thoracotomy (TCRAT) in nonselected patients with multivessel disease are reported.Methods From November 2019 to September 2021, coronary artery bypass grafting via left anterior minithoracotomy on cardiopulmonary bypass and cardioplegic cardiac arrest was performed in 102 patients (92 males; 67 ± 10 [42–87] years). Slings were placed around ascending aorta, left pulmonary veins, and inferior vena cava for exposure of lateral and inferior ventricular wall. All patients had multivessel coronary disease (three-vessel disease: n = 72; two-vessel disease: n = 30; left main stenosis: n = 44). We included patients at old age (> 80 years, 14.7%), with severe left ventricular dysfunction (ejection fraction < 30%, 6.9%), massive obesity (body mass index > 35, 11.6%), and at increased risk (EuroSCORE II > 4, 15.7%).Results Left internal thoracic artery (n = 101), radial artery (n = 83), and saphenous vein (n = 39) grafts were used for total (61.8%) or multiple (19.6%) arterial grafting. A total of 323 distal anastomoses (3.2 ± 0.7 [2–5] per patient) were performed to revascularize left anterior descending (100%), circumflex (91.2%), and right coronary artery (67.7%). Complete revascularization was achieved in 95.1%. In-hospital mortality was 2.9%, stroke rate was 1.0%, myocardial infarction rate was 2.9%, and repeat revascularization rate was 2.0%.Conclusion This novel surgical technique allows complete coronary revascularization in the broad majority of multivessel disease patients without sternotomy. TCRAT can be introduced into clinical routine safely. Long-term results remain to be investigated.
Keywords: coronary artery bypass grafting; CABG; minimally invasive cardiac surgery; minithoracotomy; cardiac; myocardial infarction